Users' perception on Maxis e-mail bill service in Klang Valley / Ahmad Helmi Mokhtar - Mokhtar, Ahmad Helmi (2005)
This paper is about a study on the users' perception of Maxis e-Mail Bill Service in Klang Valley. The main objective of this paper is to identify the users' perception level on Maxis e-Mail Bill Service in the Klang Valley area. The second objective is to investigate the relationships between the users' demographic elements and their perception level. The research began by distributing questionnaires to the respondents. The respondents consist of either the present or previous users of Maxis e-Mail Bill Service. One hundred completed questionnaires were selected in this research. The paper indicates that in average, the users have moderate perception level on the Maxis e-Mail Bill Service. Besides that, it is concluded that seven out of nine users' demographic elements have significant relationships or associations with their level of perception. It is recommended that the service providers which are implementing the e-mail bill service to improve and upgrade the service quality in terms of security and reliability concerns because these factors become the barriers for the users to adopt the latest billing technology.